REPLACEMENT OF POSTERIOR MISSING TEETH WITH PORCELAIN FUSED TO METAL (PFM) BRIDGE - Eni Rahmi (Andalas Dental Journal, 2013)
Porcelain fused to metal (PFM) bridge is the most of treatment that commonly used as a fixed partial dentures. One of the indication for PFM bridge is to replacing the loss of posterior teeth. This case report discussed about the treatment of posterior missing teeth with PFM bridge. Objective: to explain the clinical procedures of PFM bridges to treat the patient with posterior missing teeth. Case report: A 29-years old woman came to prosthodontic clinic in Faculty of Dentistry University of Padjadjaran with chief complaint of right maxillary posterior missing teeth. The treatment planning that have been choosen for this case was the porcelain fused to metal bridge due this excellent characteristic of resistence to mastication force compared with other types of bridge such as all ceramic or all acrylic bridge. Beside that, the aesthetic achievement of this kind of bridges is more excellent than all metal bridges. Disscussion: A spatial analysis, calculation the number of abutment against which used, and selected design bridge very determine the success of this treatment. In addition to that, the clinical procedures consisting of abutment teeth preparation, an accurate impression, and appropriate cementation were needed to get the satisfactory result. Conclusions: The porcelain fused to metal bridge is a appropriate option for posterior missing teeth treatment that fullfil satisfactorical biomechanical and esthetic factors.